Controlled coalitional games for cooperative mobile social networks - Niyato, Dusit (2013)
Mobile social networks have been introduced as a new efficient (i.e., minimizing bandwidth usage) and effective (i.e., minimizing the delay or maximizing the number of target recipients) way of disseminating content and information to a particular group of mobile users who share similar interests. In this paper, we investigate how the content providers and the network operator can interact to distribute content in a mobile social network. The objective of each content provider is to minimize the cost that pertains to the time used to distribute the content to the subscribed mobile users and the cost due to the price paid to the network operator for transferring the content over a wireless connection through a base station. Although the content providers can cooperate by forming coalitions for sharing a wireless connection, the network operator can control the amount of bandwidth provided over the wireless connection. We introduce a novel coalitional game model, which is referred to as the controlled coalitional game, to investigate the decision-making process of the content providers and the network operator. Numerical studies show that, given the allocated bandwidth from the network operator, the content providers can self organize into coalitions while minimizing their individual cost. In addition, the results demonstrate that the revenue of the network operator can be maximized when the bandwidth allocation is performed while considering the coalitional structure of the content providers.